CiudadaniaPlural.com: de las Humanidades Digitales al Humanismo Plural. - Moreno Sardà, Amparo; Molina Rodríguez-Navas, Pedro; Simelio Solà, Núria (Revista Latina de Comunicación Social, 2017)
The "Digital Humanities" are the result of the contributions made by Cybernetics in the Second World War. Computers made it easier for the Humanities and the Social Sciences to incorporate quantitative methods while the current technologies pose qualitative changes, modifying the relationship between producers and users of knowledge. This change will contribute to finding solutions to the problems derived from the social transformations, which demands the formulation of a new humanism. The criticism to the androcentric paradigm has allowed the conceptualisation of a History of Communication capable of addressing the implementation of mass culture and the information society, in the collective organisation as well as the vital routes of the plurality of men and women. This paradigm shift has allowed us to use the Internet and other digital resources to develop CiudadaniaPlural.com, a platform to produce stories about the network society and promote the Plural Humanism that we advocate for.